VLF Data Analysis Through Transformation Into Resistivity Value: Application tTo Synthetic and Field Data - Wahyu Srigutomo; Asep Harja; Doddy Sutarno; Tsuneomi Kagiyama (Institut Teknologi Bandung, 2005)
Transformation of VLF-EM signals, which are approximated as the real and imaginary components of the ratio between the vertical and the horizontal components of magnetic fields was carried out in this study to improve the quantitative interpretation aspect of VLF analysis. The transformation filter has been tested using synthetic data generated by a two-dimensional finite element algorithm that provides VLF responses for several models typically encountered in VLF surveys. The transformed apparent resistivity profiles show good agreement in value and pattern to those modeled by the finite element algorithm. The transformation was applied to the field data and further analysis was conducted by inverting the recorded original VLF-EM signals and the transformed apparent resistivity into a two-dimensional resistivity-depth section. From the comparison with the dc-resistivity-depth section obtained previously, the resulted resistivity section revealed the general features of the subsurface structure.